Analysis Of Changes In Learning Interest At Class X–TKJ Private Vocational School Of Al Washliyah 8 Perbaungan - Nur Aulia Fahmi; Khairul Usman (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This study aims to determine the results of the analysis of changes in learning interest in PJOK during the adaptation of new habits through changes in school principal policies in class X-TKJ students at Al Washliyah 8 Perbaungan Private Vocational School. This study will focus on efforts to review changes in student interest in learning which can then be used as a reference in implementing school policies related to learning. This study uses a qualitative method which is carried out with the researcher's analytical ability in connecting between research variables. This study focuses on data acquisition through observation activities and using a questionnaire. The data obtained were in the form of monitoring and study of PJOK learning activities during the COVID-19 pandemic for students of class X– TKJ of Al Washliyah 8 Perbaungan Private Vocational School. The data obtained based on observations are 76% of students have an interest in learning related to changes in the learning rule system. The results of the questionnaire show that students have 42%, which means that on average students are always ready and carry out the learning process well when compared to others. The 30% data shows that students often receive instructions to carry out in the learning process, while 21% and 7% of students tend to delay and have low interest in changing regulations related to PJOK learning. The conclusion from the results of the analysis of changes in learning interest in PJOK during the adaptation of new habits through changes in the principal's policy in class X-TKJ students of Al Washliyah 8 Perbaungan Private Vocational School shows that students can accept the policy. The policy changes implemented by the principal are accepted by students based on age backgrounds which are generally in the early adulthood age range. Psychologically, in early adulthood, a person is able to receive information and translate every instruction received, so the results of the analysis show that students still have a fairly good interest in learning despite changes in policies related to the learning process implemented by the school.